Existence and Asymptotic Behavior of Boundary Blow-up Weak Solutions for Problems Involving the p-Laplacian (Journal of Partial Differential Equations, 2013)
Let D⊂R^N(N ≥ 3), be a smooth bounded domain with smooth boundary ∂D. In this paper, the existence of boundary blow-upweak solutions for the quasilinear elliptic equation Δ_pu=λk(x) f (u) in D(λ > 0 and 1 < p < N), is obtained under new conditions on k. We give also asymptotic behavior near the boundary of such solutions.